Life Threatening High-Altitude Cerebral Edema and High-Altitude Pulmonary Edema in A Trekking Guide on the Kathmandu–Mansarovar Route - Bam, Niraj; Karki, Prashanna; Pokhrel, Milan; Shrestha, Bibek (Journal of Nobel Medical College, 2026)
High-altitude illness remains a critical risk for travelers to mountainous regions, particularly when rapid ascent occurs without adequate acclimatization. We describe a 52-year-old trekking guide who developed simultaneous high-altitude cerebral edema (HACE) and high-altitude pulmonary edema (HAPE) while leading a group to Mansarovar via the Kathmandu–Rasuwagadhi–Kerung overland route. Despite extensive experience at altitude, he ascended from 1,400 m to over 4,600 m within two days without prophylaxis. He presented with profound hypoxemia, dizziness, ataxia, and dry cough. Descent was delayed due to logistical barriers, and he required two days of travel before reaching a tertiary hospital. Imaging confirmed pulmonary edema, and persistent neurological deficits were consistent with HACE. Treatment with supplemental oxygen and dexamethasone led to complete recovery. This case highlights that vehicular travel does not mitigate altitude risk and emphasizes the importance of gradual ascent, prophylactic measures, and timely intervention in preventing life-threatening outcomes